Simultaneous functional photoacoustic microscopy and electrocorticography reveal the impact of rtPA on dynamic neurovascular functions after cerebral ischemia. Issue 6 (June 2018) - Bandla, Aishwarya; Liao, Lun-De; Chan, Su Jing; Ling, Ji Min; Liu, Yu-Hang; Shih, Yen-Yu Ian; Pan, Han-Chi; Wong, Peter Tsun-Hon; Lai, Hsin-Yi; King, Nicolas Kon Kam; Chen, You-Yin; Ng, Wai Hoe; et al.
The advance of thrombolytic therapy has been hampered by the lack of optimization of the therapy during the hyperacute phase of focal ischemia. Here, we investigate neurovascular dynamics using a custom-designed hybrid electrocorticography (ECoG)-functional photoacoustic microscopy (fPAM) imaging system during the hyperacute phase (first 6 h) of photothrombotic ischemia (PTI) in male Wistar rats following recombinant tissue plasminogen activator (rtPA)-mediated thrombolysis. We reported, for the first time, the changes in neural activity and cerebral hemodynamic responses following rtPA infusion at different time points post PTI. Interestingly, very early administration of rtPA (< 1 h post PTI) resulted in only partial recovery of neurovascular dynamics (specifically, neural activity recovered to 71 ± 3.5% of baseline and hemodynamics to only 52 ± 2.6% of baseline) and late administration of rtPA (> 4 h post PTI) resulted in the deterioration of neurovascular function. A therapeutic window between 1 and 3 h post PTI was found to improve recovery of neurovascular function (i.e. significant restoration of neural activity to 93 ± 4.2% of baseline and hemodynamics to 81 ± 2.1% of baseline, respectively). The novel combination of fPAM and ECoG enables direct mapping of neurovascular dynamics and serves as a platform to evaluate potential interventions for stroke.